2019
DOI: 10.1039/c9ra02277e
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of oxygen sensitivity on the molecular structures of Ir(iii) complexes and their application for photostable and reversible luminescent oxygen sensing

Abstract: The delocalization of spin populations (DSPs) could be used to describe the dependence of oxygen sensitivity on the molecular structures of Ir(iii) complexes. And excellent operational stability of an Ir(iii) oxygen sensing film is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Corresponding Ir (III) complexes all showed similar and typical absorption in THF, similar to other cyclometalated Ir (III) complexes previously reported [3]. The Ir-1 and Ir-4 complexes exhibited intense absorption bands in the UV area belong to π-π* transitions of intra-ligands (ILCT) [7,11]. Their lower energy absorption bands around 380 nm and 405 nm can be attributed to the overlap of metal-ligand charge transfer (MLCT), inter-ligand charge transfer (ILCT) and ligand-ligand charge transfer (LLCT) interactions.…”
Section: Absorption and Phosphorescence Emission-based Propertiessupporting
confidence: 82%
See 1 more Smart Citation
“…Corresponding Ir (III) complexes all showed similar and typical absorption in THF, similar to other cyclometalated Ir (III) complexes previously reported [3]. The Ir-1 and Ir-4 complexes exhibited intense absorption bands in the UV area belong to π-π* transitions of intra-ligands (ILCT) [7,11]. Their lower energy absorption bands around 380 nm and 405 nm can be attributed to the overlap of metal-ligand charge transfer (MLCT), inter-ligand charge transfer (ILCT) and ligand-ligand charge transfer (LLCT) interactions.…”
Section: Absorption and Phosphorescence Emission-based Propertiessupporting
confidence: 82%
“…The new cyclometalated iridium (III) complexes in nanocomposites made of AP200/19 and in polystyrene lm were presented by Marín-Suárez and co-workers, and the results have been found promising for the detection of low oxygen concentrations [6]. Xing et al reported that I 0 /I 100 values of the Ir (III) complexes; IrC1, IrC2, and IrC3 substituted with 4-(diphenylamine)phenyl, 4-(9H-carbazol-9yl)phenyl, and 9-phenyl-9H-carbazol-3-yl moieties were found as 33.0, 8.2 and 16.5, respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…The quantum yield of the suspension sensor 1 (NMP) was measured with Ir(ppy) 3 (quantum yield of 0.40) as a standard. 41,42 And the solid-state quantum yields of 1 (original), and 1 (ground) were measured on a HITACHI F-7000 spectrophotometer by employing an integrating sphere.…”
Section: Materials and Physical Measurementsmentioning
confidence: 99%